2022
DOI: 10.1002/ange.202201007
|View full text |Cite
|
Sign up to set email alerts
|

Theory‐Guided Regulation of FeN4Spin State by Neighboring Cu Atoms for Enhanced Oxygen Reduction Electrocatalysis in Flexible Metal–Air Batteries

Abstract: Iron, nitrogen‐codoped carbon (Fe−N−C) nanocomposites have emerged as viable electrocatalysts for the oxygen reduction reaction (ORR) due to the formation of FeNxCy coordination moieties. In this study, results from first‐principles calculations show a nearly linear correlation of the energy barriers of key reaction steps with the Fe magnetic moment. Experimentally, when single Cu sites are incorporated into Fe−N−C aerogels (denoted as NCAG/Fe−Cu), the Fe centers exhibit a reduced magnetic moment and markedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Previous studies on the CO 2 RR and ORR also showed that the adjacent metal atoms on N-doped graphene tuned the electronic spin moments of reactive metal sites, leading to increased intrinsic activity. 18,20 In addition, Mi and Guo et al also highlighted the key role of the magnetic active center in the ORR 43 and the hydrogen evolution reaction (HER). 44…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies on the CO 2 RR and ORR also showed that the adjacent metal atoms on N-doped graphene tuned the electronic spin moments of reactive metal sites, leading to increased intrinsic activity. 18,20 In addition, Mi and Guo et al also highlighted the key role of the magnetic active center in the ORR 43 and the hydrogen evolution reaction (HER). 44…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on the CO 2 RR and ORR also showed that the adjacent metal atoms on Ndoped graphene tuned the electronic spin moments of reactive metal sites, leading to increased intrinsic activity. 18,20 In addition, Mi and Guo et al also highlighted the key role of the magnetic active center in the ORR 43 and the hydrogen evolution reaction (HER). 44 Very recently, Ren and Li et al 45 reported the delicate synergetic effect of charge transfer and spin selection of magnetic single Mn atom catalysts conned in graphitic-C 3 N 4 / CeO 2 (111) for CO oxidization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations